Kompetensi Pedagogik Tenaga Pendidik dalam Menggunakan Metode Pembelajaran Pada Bidang Studi SKI di MTsN 5 Padang Pariaman - Nora Afnita; Joni Indra Wandi; Misra Melati (Institut Agama Islam Sumatera Barat, 2021)
Improving the quality of education automatically has an impact on improving the quality and competence of education, so that educational goals can be achieved properly. Education must have several competencies, and about the pedagogical competence of education must be the effect of very important lessons which also apply to Islamic cultural history lessons. The formulation of the research problem to realize educational pedagogic competence in Islamic cultural history learning, the purpose of this research is to find out how effective the educators' pedagogics are in choosing the Islamic cultural history learning method. The form and type of this research are field research using descriptive methods, data collection using observation, documentation and interview techniques that are submitted to educators in the field of Islamic cultural history and school principals. The results of this study indicate 1. Educators in the field of Islamic cultural history at MTsN 5 Padang Pariaman have used the learning method but it is still not right, 2. Educators are still not effective in using the method. 3. The impact of using the method by educators causes students to be sleepy, unable to concentrate. The conclusion of this study is that the use of methods in learning the history of Islamic culture is still less effective because the selection of learning methods is still not right. Keywords: pedagogic competence, learning methods, Islamic cultural history.